Bonding, Bridging and Linking Capital: How Social Capital was Mobilized During the PPKM Micro in Malang Raya - Chawa, Anif Fatma; Putra, Moch Hisyam; Susanti, Anik (JURNAL ILMU SOSIAL, 2023)
This article aims to explain how community based approached has been adopted during the implementation of PPKM mikro (micro restriction) which is assumed to be more effective in handling the covid-19 pandemic. The implementation of PPKM mikro involves various parties ranging from the lowest level of Indonesian government (RT/RW or households) to the central government and community members. By utilizing Putnam’s social capital perspective, this study examines how all these parties established the social relations or networks during the PPKM mikro. This study employs a case study approach to examine the implementation of PPKM mikro in Malang Raya, East Java Province. This study found that the PPKM micro has used the social capital pre-existing in neighbourhood circumference (RT/RW). This social capital was expanded and enforced during PPKM micro under the Decree of the Minister of Home Affairs No.3 of 2020 concerning PPKM micro. Moreover, this enforcement also generates all the types of social capital which are bonding, bridging and linking social capital. Bonding social capital was established at RT/RW level. Bridging social capital emerged from the relations between or inter RT/RW levels established by visual information represented by flags of different colours ranging from green, yellow, orange, to red informing the number of households confirmed with positive covid-19 in each RT/RW. Linking social capital was formed from social relations between RT/RW with the highest levels of government including the village, district, municipality/regency and central government.